Acute gastric volvulus through an unsuspected diaphragmatic hernia - Ahmed Eshiba; Mostafa Kotb; Sameh Shehata (Elsevier, 2019)
Acute gastric volvulus occurs when the stomach undergoes torsion in the thoracic cavity. It may result from an accompanying enlargement of the hiatus or a missed congenital diaphragmatic hernia (CDH). We describe a 12-year-old girl who presented to our emergency department with acute epigastric pain and non-bilious vomiting. An incidental finding of diaphragmatic hernia with hugely dilated stomach was diagnosed by plain X ray, Ultrasound (US) and Computed tomography (CT) abdomen with oral contrast. She underwent laparotomy and gastric volvulus was found. Reduction of the viscera to the abdominal cavity and repair of diaphragmatic defect was done. She recovered with accepted general condition and was discharged five days later. Keywords: Diaphragmatic hernia, Gastric volvulus